Life Satisfaction in Australia: Evidence from Ten Years of the HILDA Survey - Ambrey, C; Fleming, C (My University, 2013)
Employing data from the Household, Income and Labour Dynamics in Australia survey, this paper examines the level, determinants and distribution of self-reported life satisfaction, as well as the prevalence and severity of dissatisfaction in Australia over the period 2001–2010. Against most objective measures Australia’s economic performance during this period was exemplary. Yet our results indicate a steady decline in life satisfaction from 2003 onwards, as well as a diminishing gap between the life satisfaction of males and females. Results also suggest that inequality in life satisfaction has generally declined. Geographic heterogeneity in the distribution of life satisfaction is apparent, and a number of socio-economic and demographic factors are found to serve an important role in determining an individual’s level of life satisfaction. Measures of the extent of dissatisfaction reveal an encouraging downward trend and provide policy makers with an alternative perspective from which to assess societal welfare.
Social Indicators Research
Keywords: Satisfaction -- Life; Gender; Gender; Lifestyle; Gender; Satisfaction; Life; Gender; Lifestyle